Changes in prevalence, and factors associated with tobacco use among Bangladeshi school students: evidence from two nationally representative surveys - Tanvir Ahammed; Nasar U. Ahmed; Md Jamal Uddin (BMC, 2021)
Abstract Background Globally, tobacco kills more than nine million people per year. Annually in Bangladesh, smoking accounts for 1.2 million illnesses and over one hundred fifty thousand deaths. Worldwide, about one out of five school students smoke tobacco, and this problem is also growing significantly in Bangladesh. There is a need to address this problem. However, to the best of knowledge, no published study has been evaluated the changes in factors associated with tobacco use over time among Bangladeshi adolescent students using large, nationally representative comparable surveys. Our objective was to identify the factors associated with tobacco use among school going students, examine any changes in them over time, and explore policy options based on national surveys. Methods We analysed the data from the 2007 and the 2013 Global Youth Tobacco Survey (GYTS), a school-based survey targeting adolescents age 13-15 years (7th-9th grade), developed by the World Health Organization (WHO) and the Centres for Disease Control and Prevention (CDC). The samples were selected based on a two-stage cluster sample design. The data were collected in school classes using a self-administered anonymous survey. We applied chi-square tests and survey logistic regression models for analysing the data. Results Overall tobacco usage significantly declined from 8.4 to 6.9% over six years. The prevalence of tobacco use decreased among females (5.22 to 2.84%), those who received anti-tobacco messages (8.93 to 7.24%) and because of age restriction could not buy tobacco products (18.86 to 15.78%). Compared with the female, the odds of overall tobacco smoking among male students was 1.97 (CI: 0.99-3.92) in the year 2007 and it increased (OR = 3.07; CI: 1.56-6.04) in the year 2013. Moreover, the odds of smoking among those exposed to tobacco smoke had increased (OR = 3.26; CI: 1.46-7.29 vs 5.43; CI: 1.63-18.07) from 2007 to 2013. Conclusion There was a decline in tobacco use, especially among female students. Male students were higher tobacco user. It appeared anti-smoking campaign and age restriction policies were working.